Efektifitas Penerapan Ideal Include Discuss Educate Asses Listen Discharge Planning terhadap Average Length of Stay AvLOS Hospital Costs pada Pasien Congestive Heart Failure - Adhisty, Weny Anggraini; Yusuf, Saldy; Kaelan, Cahyono (Jurnal Keperawatan Soedirman, 2017)
The aim of the research was to determine the effect of IDEAL Discharge Planning Implementation on Average Length of Stay (AvLOS) and Hospital Cost patients with Congestive Heart Failure (CHF). The research used quasy experiment post test only non equivalent control group design. The sample was 36 respondents consisting of 18 intervention groups and 18 control groups. Data were analyzed using two methods, Mann Withney statistical test for numerical data and Fisher's Exact Test for categorical data.The results showed that there was significant effect of discharge planning implementation on AvLOS and Hospital Cost patients with CHF with p Value < 0.05 where the mean value of AvLOS group of intervention group 4.83 days was much shorter than the mean AvLOS control group extending up to 8.28 days with p 0.015. This also has implications for Hospital Cost where the mean control group is much larger that is Rp. 6,798,659.22 while in the intervention group of Rp. 3,291.54 with significance level p 0.001.